Unsur Instrinsik Yang Terkandung dalam Cerita Swarga Rohana Parwa - Karunia Dewi, Luh Putu (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2024)
The current state of Indonesian society is troubled by moral decline. This not only affects teenagers but also older people who can set an example of good behavior. A quality nation is a nation that is able to maintain its personality, provide moral education, exemplify the teachings of noble values to be preserved and developed in harmony with the progress of the times. One way is to explore and display the treasures stored in Old Javanese literary works. Based on the background above, the main problems can be raised, namely as follows: (1) What is the synopsis of the story Swarga Rohana Parwa? (2) What is the analysis of the intrinsic elements in the story Swarga Rohana Parwa? (3) What educational values are contained in the story Swarga Rohana Parwa. Swarga Rohana Parwa is one of the classic literary works in the Old Javanese language. This prose focuses on the process of human life after leaving the world based on the results of their actions.